2017
DOI: 10.3892/or.2017.5747
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of gastric cancer by extract from the tuber of amorphophallus konjac via induction of apoptosis and autophagy

Abstract: The tuber of amorphophallus konjac (TuAK) is an antitumor herb used in traditional Chinese medicine. The present study investigated the inhibitory effect of TuAK against gastric cancer and the underlying mechanisms associated with two programmed cell death pathways, apoptosis and autophagy. TuAK was extracted by organic solvents including ethanol and ligarine. The extract of TuAK, shortened as TuAKe, significantly inhibited the growth of cultured gastric cancer cell lines SGC-7901 and AGS, with IC50 of 35-45 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Therefore, inducing autophagy-associated cell death of cancer cells may be useful in cancer treatment (49)(50)(51)(52). An extract from the tuber of Amorphaphallus was reported to suppress the growth of proliferation of SGC-7901 and AGS cancer cells by induction of apoptosis and autophagy (53). Fenugreek extract also displayed anticancer effects through induction of autophagy and autophagy-associated death in human T lymphoma jurkat cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inducing autophagy-associated cell death of cancer cells may be useful in cancer treatment (49)(50)(51)(52). An extract from the tuber of Amorphaphallus was reported to suppress the growth of proliferation of SGC-7901 and AGS cancer cells by induction of apoptosis and autophagy (53). Fenugreek extract also displayed anticancer effects through induction of autophagy and autophagy-associated death in human T lymphoma jurkat cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it mainly serves either as a dietary supplement aiding in weight loss, diabetes, arterial sclerosis, and constipation, or as an emulsifier and thickener in food processing (Chen et al, 2017a; Wu et al, 2018), which corroborates the old theory of “homology of medicine and food.” In fact, many natural polysaccharides that show potent anti-tumor activity (Kim et al, 2011; Xiao et al, 2017; Zhang, 2017; Deng et al, 2018) derive from edible herbs, such as Lentinus , Cordyceps , Ganoderma lucidum , and Hericium , which themselves are also common cuisine ingredients. Recently, glucomannan extracted from Amorphophallus konjac (Chen et al, 2017a), Bletilla striata (Zhan et al, 2014), Lentinus edodes (Fujii et al, 1978), Aloe vera (Sampedro et al, 2004; Im et al, 2005; Liu et al, 2006; Im et al, 2016; Quezada et al, 2017), and Candida utilis (Kumano et al, 1985) were demonstrated to have similar effect. Moreover, according to the studies reviewed in the present research, glucomannan, mainly from these species, not only is an anti-cancer drug by itself but also works as a targeted carrier that is compatible with various bioactive compounds.…”
Section: Introductionmentioning
confidence: 60%
“…Given that tumor cells are apoptosis resistant, drugs aimed to promote apoptosis are widely used in cancer therapy (Hassan et al, 2014). Initially, studies unveiled the therapeutic effect of extract from A. konjac (AKe) on various cancers, such as colon carcinoma (Ansil et al, 2013; Ansil et al, 2014a), gastric cancer (Chen et al, 2017a), hepatoma (Ansil et al, 2014b), and breast cancer (Wu et al, 2018; Wu et al, 2019). Chen et al found that AKe could inhibit the growth of in vitro cultured gastric cancer cell lines SGC-7901 and AGS (Chen et al, 2017a).…”
Section: Glucomannan Directly Interferes With Intrinsic Tumor Cells Bmentioning
confidence: 99%
See 2 more Smart Citations